Progressive Multifocal Leukoencephalopathy Diagnosed by Metagenomic Next-Generation Sequencing of Cerebrospinal Fluid in an HIV Patient - Xia, Huan; Guan, Yuanlin; Zaongo, Silvère D.; Xia, Han; Wang, Ziyu; Yan, Zhongfang; Ma, Ping (Frontiers in Neurology, 2019)
Metagenomic next-generation sequencing (mNGS) is a novel approach to identify pathogens undetected by conventional methods. Herein, we report a case in which mNGS was used to identify John Cunningham virus from the cerebrospinal fluid sample of an HIV positive patient with progressive multifocal leukoencephalopathy.